Schizopyga alinae, a genus of pimpline parasitoid wasps (Hymenoptera: Ichneumonidae: Pimplinae) new to the Afrotropical region - Varga, Oleksandr; Reshchikov, Alexey (Zootaxa, 2018)
Schizopyga Gravenhorst, 1829 is a small genus belonging to the Polysphincta genus-group of the subfamily Pimplinae, with 12 known species worldwide (Yu et al., 2012; Matsumoto, 2016), two of them from the Afrotropical region (Gauld & Dubois, 2006).        Schizopyga species are known as parasitoids of spiders creating non-aerial webs (Clubionidae, Gnaphosidae, and Agelenidae) (Matsumoto, 2016).